Math, asked by iampranavtaparia, 7 months ago

(x + y)(8x – 16y) ÷ (x^2 – xy – 2y^
2

)​

Answers

Answered by bhowmik2018piu
1

Answer:

8

Step-by-step explanation:

(x + y)(8x – 16y) ÷ (x^2 – xy – 2y^2)

= (8x^2-16xy+8xy-16y^2) / (x^2-xy-2y^2)

= (8x^2-8xy-16y^2)/ (x^2-xy-2y^2)

= 8(x^2-xy-2y^2)/ (x^2-xy-2y^2)

=8

Answered by SWANANDKALE
0

8

Step-by-step explanation:

(x + y)(8x - 16y) = (x^2 - xy - 2y^2)

= (8x^2-16xy+8xy-16y^2)/(x^2-xy-2y^2) = (8x^2-8xy-16y^2)/(x^2-xy-2y^2)

=

= 8(x^2-xy-2y^2)/(x^2-xy-2y^2) =

=8

Similar questions